COMPUTATIONAL ANALYSIS ON HEAVE AND PITCH MOTIONS PERFORMANCE OF A HYDROFOIL SHIP - Fitriadhy, A; Amira Adam, N; Syafiq Zikry, M (Journal of Marine-Earth Science and Technology, 2020)
Hydrofoil ship usually experiences high resistance and excessive heave and pitch that may lead to downgrade her seakeeping performance. Therefore, a reliable investigation on prediction of a seakeeping performance of a hydrofoil ship in head-seas is obviously required. To achieve this objective, an analysis of Computational Fluid Dynamic (CFD) approach on hydrofoil ship motion is then proposed. Several parameters such as angle of stern foil and Froude Number have been accordingly taken into account in the simulation, where the fore foil angle is constantly 5 . In general, the results revealed that the increase of the stern foil angle was proportional to the heave motion of the hydrofoil ship. As compared to the magnitude of the stern foil angle of 5 and 10 , the heave motion of the hydrofoil ship has sufficiently decreased at the stern foil angle of 7.5, which leads to have a better seakeeping performance. Furthermore, the subsequent increase of Froude number pointing towards reduction of heave motion, which was inversely proportional to the magnitude of her pitch motion. Inherently, these have led to degrade of the hydrofoil ship seakeeping performances presented in the form of high Response Amplitude Operators (RAO). In general, this CFD simulation is very beneficial to ensure an operational effectiveness of hydrofoil design in high sea states with respect to the aforementioned design parameter.